2009
DOI: 10.1159/000242250
|View full text |Cite
|
Sign up to set email alerts
|

Management of Obstructive Uropathy Patients with Advanced Prostate Cancer – A Systematic Review

Abstract: Background: The optimal management of malignant ureteral obstruction in prostate cancer patients remains under debate and there exist no evidence-based recommendations to assist clinicians in advising patients. Material and Methods: Four databases were searched for the best available evidence for the treatment of ureteral obstruction and subsequent obstructive uropathy in prostate cancer regarding efficacy, overall survival and side effects. Treatment options considered were percutaneous nephrostomy (PCN), ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
(26 reference statements)
0
6
0
1
Order By: Relevance
“…2 A larger review looking at prostate cancer suggested there was no consensus on how to manage BUO in advanced disease. 3 Individual case series on breast and esophageal cancer suggested ureteric diversion reversed the kidney injury and allowed further treatment of the systemic disease. 4,5 Despite the controversy in the management of this condition and the accepted poor prognosis, most patients receive percutaneous nephrostomy tubes (PNTs), retrograde ureteric stents or both.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A larger review looking at prostate cancer suggested there was no consensus on how to manage BUO in advanced disease. 3 Individual case series on breast and esophageal cancer suggested ureteric diversion reversed the kidney injury and allowed further treatment of the systemic disease. 4,5 Despite the controversy in the management of this condition and the accepted poor prognosis, most patients receive percutaneous nephrostomy tubes (PNTs), retrograde ureteric stents or both.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown both stents and nephrostomy tubes are effective methods to restore kidney function after ureteric obstruction. 2,3,10,[16][17][18][19] Advancements in and availabil- There was a trend toward a decreasing percentage in the number of patients presenting with BUO secondary to cervical cancer compared with 1982. It is possible that aggressive screening for cervical cancer over the past 25 years contributed to this observation.…”
mentioning
confidence: 99%
“…Furthermore, baseline characteristics between the single polymeric IUS and PCN groups, as well as other contributing factors, such as overall survival, often differ between studies. 59 Management of MUO by either single polymeric IUS or PCN drainage results in similar complication rates. Ku and colleagues 60 demonstrated no significant difference in the incidence of overall complications between the two groups (11% for the stent group vs 8.8% for the PCN group).…”
Section: Comparison Of Endoscopic Options For Upper Tract Obstructionmentioning
confidence: 96%
“…Relevant literature and expert clinicians (M.P., H.P., N.C., J.S.A.G.) were consulted to identify relevant ICD-10 and OPCS-4 codes following the steps detailed below [12,13] (Appendix 1).…”
Section: Codingmentioning
confidence: 99%